Changes in the Carotene Content of Nantes Type Carrots during Storage - Némethy, H.; Fehér, M. (International Journal of Horticultural Science, 2002)
Changes in carotene content occurring during winter storage in Nantes type carrot hybrids grown on soils of different quality (sand and loam) have been investigated. The carotene content of the samples grown in a rainy year (1999) was lower than that of the samples grown in a dry year (2000). Lower carotene content was found in carrots produced on sandy soil (Szatymaz) than on loam soil (Tordas). The increase in carotene content (2-11 mg1100 g) measured at the end of winter storage was related to the season's character.